Special Education is Broken - Rader, Lacie (Journal of the American Academy of Special Education Professionals, 2010)
The author describes her experience as special education teacher at Berkeley High School (BHS), an urban school with over three thousand students, and how she began to question the way the school defines disability. The diversity of any large urban school has its benefits, but the size itself will always be the downfall when the school focuses on lofty dreams of cultivating Ivy League students while developing the national reputation for academic rigor. Without fail, students who are on the lower end of the socio-economic spectrum will fall behind because the school’s focus does not take into account the diversity it encourages. Even though ten percent of BHS students have IEPs because they cannot cope with the standards of the school, few changes have been made in the curriculum, vocational skills classes have not been added, the graduation standards remain the same and teachers are encouraged to keep moving quickly through materials in order to accommodate and challenge students on the other end of this spectrum. Special education seemed to be housing all of the students who could not get an "A" in overcrowded high level English classes taught by teachers who are far more interested in finishing up their PhD than teaching at high school. The author asks the question: why not address the situation for what it is; the students that make up the lower socioeconomic end of our schools are not able to get their needs met within the college prep structure? The special education program makes this face-to-face with the facts confrontation a less pressing need. Yet the special education department, accompanied with paperwork, psychologists and insufficient funding is not a solution to the problem.